ASSESSING THE EFFECTS OF AN OCCLUSAL DISHARMONY ONTO THE DENTO-MAXILLARY SYSTEM USING THE FINITE ELEMENT METHOD - Popa Diana Angelica; Mercuț Veronica; Popescu Adrian Marcel; Târtea Daniel Adrian; Castravete Ștefan; Rîcă Gabriel Radu; Scrieciu Monica; Amărăscu Marina Olimpia; Vlăduțu Diana-Elena (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study. To obtain two virtual models of dento-maxillary system with a detailed representation of the TMJ, in order to highlight through the finite element method the way in which the stresses are distributed on the components of the dento-maxillary system, when the dental occlusion is modified. Material and methods. To obtain the geometric data for the mandibular and maxillary structures, a CT scan of an open-mouthed skull was used, resulting in a series of 2D DICOM images. The transformation of these 2D DICOM images into a 3D format was performed using MIMICS software. The TMJ was reconstructed in the computer-aided design software based on established assumptions and reference data. Computational analysis of the mandibular structure involved discretizing its geometry into finite elements, a widely used numerical technique that divides complex structures into smaller, manageable elements for computational analysis. In this study, FEM was adopted to facilitate the simulation and evaluation of biomechanical responses in dento-maxillary system. Results. The base model served as a reference, depicting the structural response of the mandible to mouth closing forces without any additional intervention elements. The modified model by incorporating a 1 mm plate between the 1st lower molar and the antagonistic premolar induced a change in mandibular dynamics. Conclusions. The study allowed to obtain a virtual model of dento-maxillary system with faithful reproduction of the components of the TMJ and to evaluate the demands on the dental arches and the TMJ in the case of the basic model and the modified one. The inclusion of a premature contact at the level of one hemiarch led to the redistribution of pressure forces at the level of the dental arches and stress in the two TMJs.